Pengaruh pengencer Tris Aminomethane kuning telur yang disuplementasi sari kulit Manggis (Garcinia Mangostana) terhadap kualitas semen Sapi Limousin selama penyimpanan suhu dingin 50C - Effendi, Fredyan Isnan; Wahjuningsih, Sri; Ihsan, M. Nur (Faculty of Animal Science, Universitas Brawijaya, 2015)
The purpose of this research was to determine the dose of mangosteen rinds juice (0%, 2%, and 4%) in a diluent Tris Aminomethane-egg yolk. The fresh semen was collected once a week using an artificial vagina from five Limousin bulls aged 8 to 11 years old with a body weight of 895-1034 kg. The research method was experimental laboratory using a randomized block design with 3 treatments and 10 replications. If there were significant influences among the variables, it would be then tested by Duncan’s Multiple Range test method. The result showed that Tris Aminomethane-egg yolk diluent with 4% of mangosteen rinds juice suplementation had significant differences (P<0.05) on the sperm quality kept for 72 hours in the cold storage in terms of the percentage of sperm motility and sperm viability. It also had a significant difference (P<0.05) on sperm abnormality particularly within the 1st hour. It can be concluded that the addition of 4% mangosteen rinds juice in Tris Aminomethane-egg yolk diluent could protect Limousin bull semen quality (motility, viability and abnormality) after stored for 72 hours at 50C. Keywords: Abnormality, liquid semen, mangosteen rind, motility, viability